Sewage sludge management: A case study - Dorota Miłek; Jolanta Latosińska; Zbigniew Dyk (Economic and Environmental Studies (E&ES), 2018)
Currently, the constantly growing problem in the municipal economy is the management of sewage sludge. According to the law, it is the local government that is responsible for the utilization of sewage sludge and is obliged to select optimal technologies, obtain funds and convince the community of the necessity of its implementation. BIONOR Company has developed an innovative concept for the separation and utilization of sewage sludge in the BIONOR SLUDGE compact installation. This innovative technology is effective from the perspective of reducing the waste amount and can be used to solve the problem of utilization of sewage sludge produced in small, rural wastewater treatment plants. The aim of the article is the characterization of the BIONOR SLUDGE technology, a comparative analysis of costs of sludge disposal using a variety of methods and an indication of the importance of sludge management for the local development. To achieve the goal set in the article, a discriminative method was used - a description of the BIONOR SLUDGE technological line as well as a case study method - a comparative analysis of the costs of operation of BIONOR SLUDGE technological line and the costs of landfilling and utilizing of sewage sludge. The research results confirm that the monthly operational costs of the BIONOR SLUDGE technological line are lower than the costs of monthly landfilling or disposal. For potential municipalities, the introduction of BIONOR innovative technology is economical. Moreover, its usage is currently essential for many municipalities due to the introduction of a ban on landfilling of this type of waste from 1 January 2016. This technology can be used to solve the problem of utilization of sewage sludge generated in small, rural wastewater treatment plants.
Keywords: O18; O44; 330; sludge management; local development; BIONOR SLUDGE technology